Relationship between mature software engineering practices and agility practices - Ruiz de Mendarozqueta, Álvaro (2022)
This paper reports on research work on Argentinean software development organizations. The analysis provides insights into the profile of the companies regarding the usage of agile methods and software engineering practices trends, their motivations, and drivers. The conclusions can be used to understand what drivers facilitate the understanding of bonds between both in order to increase their competitiveness in domestic and off-shore markets.